Assessment of proportion and prescribing trends of coronary artery diseases in a tertiary care hospital, Kerala: a prospective observational study - V. S., Sreelekshmi; Sebastian, Philip John; C., Shamna; Babu, Neenu; R., Nithin Manohar (International Journal of Advances in Medicine, 2020)
Background: The aim of the study is to assess the proportion of types of coronary artery diseases and to analyze the trends of drug prescribing in coronary artery disease (CAD) by checking the compliance with the standard guidelines provided by the American College of Cardiology Foundation / American Heart Association (ACCF/AHA). Methods: A prospective observational study was conducted in the department of Cardiology for a period of 6 months. A total of 94 patients with varied categories of CAD were screened and analyzed. Study related data was collected from case records and by a structured interview. Data analysis was done by analyzing the prescribing trends of drug and assessing the proportion of CAD. Results: The current study found that most of the patients were of the age group of 61-70 years. The proportion of Non-ST segment elevation myocardial infarction (NSTEMI) was remarkably higher in patients with CAD (55.3%) followed by ST-elevated myocardial infarction (STEMI) (39.4%) and Unstable angina (5.3%). Chi square test shows that prescription of Antiplatelets were apparent in all the prescriptions (100%), followed by Statins (Atorvastatin 98.9%), Antihypertensives (94.7%), Anticoagulants (90.4%), Nitrates (76.6%), Antidiabetics (75.5%) and Potassium channel opener (Nicorandil 36.2%). By analyzing the prescription, it was observed that most of the drugs were prescribed rationally according to the standard treatment guidelines (ACCF/AHA). Conclusions: This study provides an overall insight of proportion of CAD and prescribing pattern in patients with CAD which reveals the rational prescribing of drugs in accordance with the standard guidelines.